Improving Reading Literacy at Primary School State 078141 Tetezou Through the Campus Teaching Program Batch 3 - Inka Nora Audea; Sanggam Pardede; Dapot Tua Manullang; Nenni Triana Sinaga; Fatiatulo Buulolo (Fakultas Pertanian, Universitas Samudra, 2022)
The Independent Teaching Campus Learning Program (MBKM) organized by the Ministry of Education and Culture. The Campus Teaching Program is currently the third batch, which is assigned to assist teachers in teaching, especially improving reading literacy. Because there are still many students who read and do not even know letters. One of the schools where the Teaching Campus is located is SD Negeri 078141 Tetezou which is located in Tetezou Village, Lahusa District, South Nias Regency, Prov. North Sumatra. The goals of the Pioneer Teaching Campus include increasing empathy or social space for existing problems, honing skills for thinking and understanding, developing insight, and soft skills, increasing the role and contribution and dedication of students to national education. The Pioneer Teaching Campus (KMP) is an activity which is carried out for 5 months that supports students in implementing the Printis Teaching Campus program directly into the real world. In this activity students help teachers teach, adapt technology, and help school administration and teachers. And the results of this experience, the author can conclude that this program is very helpful for teachers or schools, where this program is very useful and very beneficial for students.